Pedagogical content knowledge and teaching of philosophy - Castro, Lizeth Ximena; Cruz, Iván Darío; Ojeda, Manuel Alejandro (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The results of the research project Assessment of the teaching of philosophy in  Colombia between practice and experience are presented, based on epistemological problematizations that delimit the object of general didactics and on the encounter with the emerging pedagogical content knowledge [PCK], which raises the need to configure the didactics of philosophy and its conceptualizations. Park and Oliver’s model is used to analyze the PCK in philosophy classes. The intention is to assess the pertinence of this model in the teaching of philosophy and to find potentialities and limitations when executing a model that highlights the philosophical knowledge that exists in spaces and times of formation, which allows reconsidering the model itself and modifying it in order to make it a field of schooled knowledge.